2000
DOI: 10.1002/1522-726x(200010)51:2<205::aid-ccd16>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Left main coronary artery aneurysm: Sealing by stent graft and long-term follow-up

Abstract: We describe the implantation of a stent graft to seal off the left main coronary artery aneurysm of a 64-year-old man with guidance by intravascular ultrasound. The aneurysm was successfully sealed off. At 6-month and 1-year follow-up, a small residual aneurysm reappeared, which was treated conservatively. The technical issues in closing this aneurysm and the management of the residual aneurysm are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Recently the use of covered stents has become an effective option. 7 Mild mitral valve prolapse had been documented in this lady 19 years ago, and the valve was preserved, as is frequently done. 7 Pyeritz et al showed that twice as many females demonstrated worse mitral valve function with time 8 thus accounting for the gradual deterioration in the clinical status of our patient over the last 4 years.…”
Section: Commentmentioning
confidence: 86%
“…Recently the use of covered stents has become an effective option. 7 Mild mitral valve prolapse had been documented in this lady 19 years ago, and the valve was preserved, as is frequently done. 7 Pyeritz et al showed that twice as many females demonstrated worse mitral valve function with time 8 thus accounting for the gradual deterioration in the clinical status of our patient over the last 4 years.…”
Section: Commentmentioning
confidence: 86%
“…If pharmacological treatment fails, then a surgical approach is proposed or an intra-coronary stent implanted. The surgical approach involves the plastic correction of the coronary vessel aneurysm using part of a vein 7 or of an artery 8 or stent implantation 9 or covered stent, plastic correction ligation with bypass graft.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown the feasibility in vein grafts (2,4,9) and to seal perforation both in native vessels and in vein (5,7,9). There have been several case reports showing the feasibility of placing a stent graft in patients with coronary aneurysms (1,7,11,12,15,26). From these reports it is possible that there are some niches for the stent graft, particularly to seal perforations.…”
Section: Discussionmentioning
confidence: 99%
“…Stent grafts have been available on the European market since 1997 and they have been suggested to be used for special occasions like treatment of coronary aneurysms, to seal perforations and to prevent peripheral embolization in old venous bypass grafts (1,2,4,5,7,9,11,12,15,26). Stent grafts have only been used in native coronary arteries in a few patients (16).…”
mentioning
confidence: 99%